Bio-Evaluation of 99mTc-Labeled Homodimeric Chalcone Derivative as Amyloid-β-Targeting Probe - Mann, Garima; Chauhan, Kanchan; Kumar, Vikas; Daksh, Shivani; Kumar, Nikhil; Thirumal, M.; Datta, Anupama (Frontiers in Medicine, 2022)
Chalcone derivatives have been successfully utilized for a range of biological applications and can cross the blood–brain barrier easily. β-amyloid-specific bis-chalcone derivative, 6,9-bis(carboxymethyl)-14-(4-[(E)-3-(4-(dimethylamino)phenyl)acryloyl]phenoxy)-3-(2-[(2-(4-[(E)-3-(4-(dimethylamino)phenyl)acryloyl]phenoxy)ethyl)amino]-2-oxoethyl)-11-oxo-3,6,9,12-tetraazatetradecanoic acid, DT(Ch)2, was analyzed using molecular modeling to explain the binding modes of the ligand with amyloid fibril and monomer followed by 99mTc-complexation in 95% yield and 98.7% efficiency. High-binding specificity of the radiocomplex was established following in vitro evaluation against 100-fold excess of DT(Ch)2. 99mTc–DT(Ch)2 exhibited <3% trans-complexation in human serum after 24 h, indicating high stability. A fast clearance rate in pharmacokinetics studies displayed a biphasic pattern with t1/2(F) = 30 min ± 0.09 and t1/2(S) = 4 h 20 min ± 0.06. In vivo single-photon emission computed tomography (SPECT) imaging in rabbits reiterated the pharmacokinetics data with initially high brain uptake followed by rapid washout. Biodistribution studies confirmed the initial brain uptake as 1.16 ± 0.02% ID/g after 2 min and the brain2min/brain30min ratio was 3.74. Radioactivity distribution in the brain was >40% in the cingulate cortex followed by >25% in the hippocampus, a distribution pattern aligned to Alzheimer’s affected brain regions. Radiocomplex also displayed rapid plasma clearance followed by hepatobolic and renal modes of excretion.